Improving the learning of Computational Fluid Dynamics (CFD) using ansys fluent - Ismail, Zurita; Laham, Mohamed Faris; Maarof, Saleha; Tamchek, Nizam (NeuroQuantology, 2022)
Physics concepts and phenomena taught in college and university always pose significant challenges even to excellent teachers. The subject required a deep understanding of many mathematical solving techniques together with understanding physics concepts and equations